Molecular detection of fungal and bacterial DNA from pustules in patients with palmoplantar pustulosis: special focus on Malassezia species. (1st January 2020) - Matsumoto, Y.; Harada, K.; Maeda, T.; Egusa, C.; Hirano, H.; Okubo, Y.; Tsuboi, R.
Summary: Background: Palmoplantar pustulosis (PPP) is a distinct, chronic skin disorder characterized by intraepidermal pustules on the palms and soles. It is hypothesized that microorganisms on the skin might induce the symptoms of PPP via inflammatory cell activation. However, the microbiota has not been studied in detail because of the assumption that the pustules in PPP are sterile. Aim: To elucidate the role of microorganisms in pathogenesis of PPP. Methods: PCR analysis was performed of microbial DNA fragments in the pustules of patients with PPP. The sequence of the D1/D2 LSU 26s rRNA gene and that of the 16S rRNA gene was used for fungal and bacterial DNA detection, respectively. Results: In total, 71 samples were carefully collected from the pustules of patients with PPP. Fungal DNA bands were detected in 68 samples, and fungi including Malassezia spp. were identified in 30 of 71 samples (42.3%). Malassezia restricta was the most frequently encountered fungus (14/71; 19.7%). However, bacterial DNA was not detected by the methods used. Furthermore, identical fungal DNA was not detected in the outer lid of the pustules, suggesting that the fungi detected within the pustule did not derive from contamination via the skin surface. Conclusions: In the present study, we demonstrated for the first time that certain pustules in patients with PPP contain fungal DNA fragments, especially those of Malassezia spp. Our findings provide new insights on the role of skin microbiota in the pathogenesis of PPP.